A qualitative study exploring public perceptions on the role of community pharmacists in Dubai - Khalid Rayes, Ibrahim; Hassali, Mohamed Azmi; Abduelkarem, Abduelmula R. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Background: The role of community pharmacists is very important due to their access to primary care patients and expertise. For this reason, the interaction level between pharmacists and patients should be optimized to ensure enhanced delivery of pharmacy services. Objective: To gauge perceptions and expectations of the public on the role of community pharmacists in Dubai, United Arab Emirates (UAE). Methods: Twenty five individuals were invited to participate in 4 separate focus group discussions. Individuals came from different racial groups and socioeconomic backgrounds. Interviews were audio-recorded and transcribed. Using thematic analysis, two reviewers coded all transcripts to identify emerging themes. Appropriate measures were taken to ensure study rigor and validity. Results: All facilitators and barriers that were identified were grouped into 5 distinct themes. The pharmacist as a healthcare professional in the public mind was the most prominent theme that was discussed in all 4 focus groups. Other themes identified were, in decreasing order of prevalence, psychological perceptions towards pharmacists, important determinants of a pharmacist, the pharmacy as a unique healthcare provider, and control over pharmacies by health authorities.